Satisfaction with access and quality of healthcare services for people with spinal cord injury living in the community. (2nd January 2020) - Ronca, Elias; Scheel-Sailer, Anke; Koch, Hans Georg; Essig, Stefan; Brach, Mirjam; Münzel, Nadja; Gemperli, Armin; ,
Abstract : Objective: To identify barriers to access healthcare services and reveal determinants of satisfaction with healthcare services in people with chronic spinal cord injury (SCI). Design: Cross-sectional survey. Setting : Community setting in Switzerland. Participants : People with chronic SCI. Interventions : Non-applicable. Outcome Measures : Questionnaire-based evaluation of availability and quality of healthcare services for secondary health conditions, satisfaction with fulfillment of healthcare needs, and preference for care from a hypothetical service provider with limited specialized SCI care expertise but in close proximity over comprehensive care from an existing specialized SCI center located at a greater distance. Results: Close to three-quarter of participants (70%) indicated satisfaction with healthcare services received for SCI related health conditions. Elderly individuals (61+ years old) rated the availability and quality of healthcare 6% to 11% higher than younger individuals. The perceived fulfillment of healthcare needs was lower in people with incomplete paraplegia (odds ratio (OR) 2.11, 95%-credibility interval (CI) 1.18–3.84), chronic pain (OR 1.85, CI 1.12–3.08), insufficient access to long distance transportation (OR 5.81, CI 2.74–12.82), and longer travel distances to specialized SCI centers. Conclusion: Perceived inadequateness of access to healthcare services was partly related to transportation barriers, suggesting that outreach services or support with transportation are possible solutions. People with incomplete paralysis and pain consistently rated the fulfillment of care needs associated with SCI less favorably, pointing to the need for enhanced advocacy for this vulnerable groups.